Functional properties in vitro and physiological effects in vivo of new sources of dietary fiber in Holtzman rats [Propiedades funcionales in-vitro y efectos fisiológicos in-vivo sobre ratas Holtzman de dietas con nuevas fuentes de fibra] - Vilcanqui-Pérez, Fulgencio (2018)
The endosperm of tara seeds (EST) and powder from the leaves of Agave americana (HAA) were evaluated as new sources of dietary fiber, using wheat bran (ST) as a reference. In vitro experiments were carried out to determine functional properties and in vivo experiments were used to determine the physiological effects of fed Holtzman rats with diets with 6% of each fiber source. Endosperm of tara had 32.2% solubility, 45.0 and 47.9 g/g absorption and water retention capacity, respectively, and 46 ml/g swelling, values significantly higher than wheat bran (p< 0.01). On the other hand, Agave had higher adsorption capacity of oil than wheat bran (6.38 g/g vs. 5.27 g/g; p< 0.01). Diets with endosperm of tara, were 8.76% of fecal fat, a value that exceeded that of wheat bran (p< 0.01); however, there was no effect on body weight of the rats. Agave increased fecal volume and reduced (p< 0.01) intestinal transit time from 14.9 to 10.4 h. Endosperm of tara retained and eliminated fat from the diet through the feces; on the other hand, the powder of Agave leaves reduced intestinal transit time. © 2018, Sociedad Chilena de Nutricion Bromatologia y Toxilogica. All right reserved.